Understanding rural-urban transitions in the Global South through peri-urban turbulence - Hutchings, Paul; Willcock, Simon; Lynch, Kenneth; Bundhoo, Dilshaad; Brewer, Timothy R.; Cooper, Sarah; Keech, Daniel; Mekala, Sneha; Mishra, Prajna Paramita; Parker, Alison; Shackleton, Charlie M.; Venkatesh, Kongala; et al. (Springer, 2022)
Much previous research has problematized the use of a binary urban–rural distinction to describe human settlement patterns in and around cities. Peri-urban zones, on the edge of urban settlements, are important both in the sheer magnitude of human population and in terms of being home to vulnerable populations with high rates of poverty. This Perspective presents a framework that conceptualizes rural–urban transition through the prism of shifts in natural, engineered and institutional infrastructure to explain the processes of rapid change and the dip in service provision often found in peri-urban areas in the Global South. We draw on examples related to the provision of water and sanitation to illustrate the theory and discuss its implications for future research on the peri-urban. A research agenda is set out that emphasizes the importance of studying early warning signs of service dips using systems theory concepts such as flickering and critical slowing down. Through such approaches, research can better predict and explain what we call peri-urban turbulence and inform the development of mitigation strategies to reduce the vulnerabilities that peri-urban residents too often face during periods of rural–urban transition.
Keywords: Developing world; Interdisciplinary studies; Socioeconomic scenarios; Sustainability